Galician Migrations: A Case Study of Emerging Super-diversity (Migration, Minorities and Modernity,, 2018)
This focused case study analyses the roots of super-diversity in a place where immigration is an emerging phenomenon, Northwestern Spain (Galicia). It is characterized by a mostly rural population, an aging demographic, and a historically depressed economy. Yet the region has recently experienced a significant increase in immigration - a reversal of the region's historically pronounced trend of emigration. To understand immigration in its early stages, this book takes a historical approach that focuses on diversities that go beyond nationality. It explores local yet international phenomena such as different patterns of return migration, transnational community and familial relationships, and niche labour markets. The book takes a broad interdisciplinary perspective, drawing on sociology, anthropology, history, sociolinguistics, literature, and education, to provide a detailed case study analysis. While the case is specific, many other geographic regions will share some of the factors the book explores. Understanding how these factors interact will provide a useful point of contrast for analysing them in a range of other international contexts. .